Extraction, Purification, Component Analysis and Bioactivity of Polyphenols from Artemisia dracunculus L. - Lin Chen; Buhailiqiemu Abudureheman; Omar Anwar; Emran Abdugini; Jianlin Zhang; Rui Tang; Zhihui Gao; Haibo Pan; Xingqian Ye (Foods)
A. dracunculus L., is a species of traditional Chinese medicine herbs, widely distributed northwestern China and used as antidiabetic, antibacterial etc., but the active compounds and their abundance have not been systematically investigated. This research focused on the following: (i) optimizing polyphenol extraction/purification from A. dracunculus; (ii) UPLC-QE-based profiling of polyphenolic composition; (iii) FT-IR-assisted structural elucidation; and (iv) functional assessment of antioxidant and antibacterial properties. The results showed that the highest extraction yield of crude polyphenols of A. dracunculus (CPA) reached 5.02 ± 0.04% at an ethanol concentration of 70% of 70 °C with a solid-to-liquid ratio of 1:20 (g/mL). The D101 macroporous resin is the best one for polyphenolpurification of A. dracunculus (PPA), with a purification efficiency of 60.48 ± 1.87%. UPLC-QE analysis identified 36 polyphenolic compounds in PPA, in whic the content of protocatechuic acid is the highest at 1338.05 ± 1.83 ng/mg. The absorption peaks at 1691 cm−1 (carbonyl, C=O), 1605 cm−1and 1518 cm−1 (aromatic C=C), as well as 1275 cm−1 and 1369 cm−1 (C-O stretching), indicated the presence of phenolic acids, flavonoids and tannins in PPA by FT-IR. PPA exhibited significant antioxidant activity, which reached 81.73 ± 1.43% for DPPH, 87.11 ± 1.57% for hydroxyl and 85.74 ± 1.52% for ABTS+. It also demonstrated strong antibacterial activity against nine common pathogenic bacteria, but not to Escherichia coli. A. dracunculus polyphenols demonstrate potent bioactive properties, suggesting potential applications in functional foods and natural preservatives.